PEMBUATAN MINUMAN INSTAN FUNGSIONAL DARI BIOAKTIF POD HUSK KAKAO - Wasmun, Herwanto; Rahim, Abdul; Hutomo, Gatot Siswo (AGROTEKBIS, 2016)
This research consists of two stages in which the first stage aims to find out the weight of the best cocoa pod husk powder that can be produced instant cacao pod husk beverages. The results of the analysis of the antioxidant capacity levels of total phenol showed that the use of dried cocoa pod husk by ethanol solvent has the highest level of both total phenols and antioxidant capasity. The second phase activity aims to find out the levels of total phenols and antioxidant capacity of instant beverages from various extracts of cocoa pod husk. This study used a completely random design (CRD) with one factor which was consisting of four levels namely cocoa pod husk weight 5 g, 10 g, 15 g and 20 g. Maltodextrin 20 g and 10 g of sucrose was added to thicker the instant beverage. The analysis showed that the highest of total phenols and antioxidant capacity in the drink when used 20 g of cocoa pod husk. The best phenols and antioxidant capacity content was from 10 g cocoa pod husk extratraction thus this amount has to be used as standard to produce this instant drink.Key Word: Extraction, Instant Drink, Pod husk.ABSTRAK